Genomic patterns of diversity and divergence of two introduced salmonid species in Patagonia, South America. (6th March 2017) - Narum, Shawn R.; Gallardo, Pablo; Correa, Cristian; Matala, Amanda; Hasselman, Daniel; Sutherland, Ben J. G.; Bernatchez, Louis
Abstract: Invasive species have become widespread in aquatic environments throughout the world, yet there are few studies that have examined genomic variation of multiple introduced species in newly colonized environments. In this study, we contrast genomic variation in two salmonid species (anadromous Chinook Salmon, Oncorhynchus tshawytscha, 11, 579 SNPs and resident Brook Charr Salvelinus fontinalis, 13, 522 SNPs) with differing invasion success after introduction to new environments in South America relative to populations from their native range in North America. Estimates of genetic diversity were not significantly different between introduced and source populations for either species, indicative of propagule pressure that has been shown to maintain diversity in founding populations relative to their native range. Introduced populations also demonstrated higher connectivity and gene flow than those in their native range. Evidence for candidate loci under divergent selection was observed, but was limited to specific introduced populations and was not widely evident. Patterns of genomic variation were consistent with general dispersal potential of each species and therefore also the notion that life history variation may contribute to both invasion success and subsequent genetic structure of these two salmonids in Patagonia.